Lactiplantibacillus plantarum P101 Ameliorates TiO2 NP-Induced Bone Injury in Young Rats by Remodeling the Gut Microbiota and Inhibiting the Production of Pro-Inflammatory Cytokines - Xie L; Feng L; Tang X; Xu Y; Xu H; Liu Y (International Journal of Nanomedicine)
Lixin Xie,1,* Lihua Feng,1,* Xiaomin Tang,1 Yunping Xu,1 Hengyi Xu,2 Yang Liu1 1Department of Pediatrics, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, People’s Republic of China; 2State Key Laboratory of Food Science and Resources, Nanchang University, Nanchang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hengyi Xu, State Key Laboratory of Food Science and Resources, Nanchang University, 235 Nanjing East Road, Nanchang, 330047, People’s Republic of China, Tel +0086-791-8830-4447-ext-9520, Fax +0086-791-8830-4400, Email kidyxu@163.com; HengyiXu@ncu.edu.cn Yang Liu, Department of Pediatrics, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, No. 1 minde Road, Nanchang, 330006, People’s Republic of China, Tel +86-791-8631-1209, Email ocean3166@yeah.netPurpose: To evaluate the therapeutic effect of oral administration of Lactiplantibacillus plantarum P101 (P101) on skeletal injury in young rats exposed to titanium dioxide nanoparticles (TiO2 NPs), and explore the potential mechanism.Methods: Four-week-old male rats were orally administration to TiO2 NPs and supplemented with P101 2 hours later for 4 weeks. The growth and development, food intake, bone metabolism and serum inflammatory markers of the rats were evaluated. Their tibias were observed and evaluated using microcomputed tomography (micro-CT), tartrate-resistant acid phosphatase (TRAP) staining, immunohistochemistry (IHC) and real-time quantitative PCR (RT-qPCR). We observed the tibia growth plate using safranin and fast green staining. 16S rDNA sequence analysis of fecal samples was performed to observe changes in the gut microbiota.Results: Our results showed that TiO2 NPs can lead to bone growth inhibition and osteoporosis, induce intestinal flora imbalance, and induce inflammation in young rats. Further mechanistic studies suggested that TiO2 NPs disrupts intestinal flora and increases serum IL-1β levels, which increased the expression of RANKL in bone, thereby enhancing osteoclast differentiation and function, leading to bone loss. Through a P101 supplementation experiment, we found that P101 ameliorated the inflammation and osteoporosis on bone caused by TiO2 NPs.Conclusion: This study showed that the mechanism by which P101 alleviates bone damage caused by TiO2 NPs may be through restoring intestinal microbial homeostasis and inhibiting inflammatory response. Keywords: TiO2 NPs, P101, young rats, intestinal flora, bone injury, IL-1&#x03B2